Psoriasis: Embarking a dynamic shift in the skin microbiota. (23rd June 2021) - Gupta, Mrinal; Weinberg, Jeffrey M.; Yamauchi, Paul S.; Patil, Anant; Grabbe, Stephan; Goldust, Mohamad
Abstract: Recent interest has arisen regarding the role of microbiome and its composition in the pathogenesis of psoriasis. Numerous studies have shown that there are alterations in skin flora arrangement between normal individuals and psoriatic patients. Psoriasis exacerbation could be interconnected with epidermal or mucosal colonization with streptococci, Malassezia, Staphylococcus aureus, or Candida albicans . The role of cutaneous and gut microbiome in psoriasis pathogenesis has recently been studied in both human and animal models. In this review, we try to evaluate various pathogenic mechanisms linking the microbiota and psoriasis. The literature research included peer‐reviewed articles which included clinical trials, original reports, and scientific reviews. MEDLINE and PubMed databases were searched from January 1990 to March 2021, including the reference lists of articles meeting our criteria.